The Green Revolution in a macroeconomic perspective: the Philippine case - Bautista, Romeo M. (International Food Policy Research Institute, 1995)
This paper analyzes the income and equity effects of the dramatic growth in rice yield in the Philippines during the green revolution period 1965-1980 using a modified Social Accounting Matrix (SAM) framework. Proportionately larger income benefits are found to accrue to the large-farm than the small-farm households, indicating a negative equity effect under the historical policy regime and economic structure. The results of counterfactual simulation involving a more active promotion of small-farm production point to a complementarity, rather than a tradeoff, between the twin objectives of growth and equity.